2008
DOI: 10.3920/jcns2008.x088
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain performance measurement: the case of the traditional food sector in the EU

Abstract: Abstract:The objective of this study is to develop a sound measurement instrument of traditional food supply chain performance integrating the perspectives of different stakeholders. Therefore first, stakeholders' goals are generalized via focus groups and individual interviews. Second, stakeholders' goals are consolidated, based on their specificity and conflicting/divergent nature and as a result, supply chain goals are developed. Third, potential performance indicators are listed, supporting the developed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Aramyan, Oude Lansink, Van der Vorst, & Van Kooten, 2007;Fischer et al, 2008;Hardman, Darroch, & Ortmann, 2002;Pannekoek, Van Kooten, Kemp, & Omta, 2005). Traditional food products as a food category are not yet extensively analysed from the chain perspective, with some notable exceptions (Gellynck & Kühne, 2008;Gellynck, Molnár, & Aramyan, 2008;Raynaud, Sauvee, & Valceschini, 2005). The integration of chain partners in the innovation process enhances the capacity to innovate and reduces the risks involved in implementing innovation (Earle, 1997;Gellynck & Kühne, 2008;Omta, 2002;Pittaway et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Aramyan, Oude Lansink, Van der Vorst, & Van Kooten, 2007;Fischer et al, 2008;Hardman, Darroch, & Ortmann, 2002;Pannekoek, Van Kooten, Kemp, & Omta, 2005). Traditional food products as a food category are not yet extensively analysed from the chain perspective, with some notable exceptions (Gellynck & Kühne, 2008;Gellynck, Molnár, & Aramyan, 2008;Raynaud, Sauvee, & Valceschini, 2005). The integration of chain partners in the innovation process enhances the capacity to innovate and reduces the risks involved in implementing innovation (Earle, 1997;Gellynck & Kühne, 2008;Omta, 2002;Pittaway et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Through the use of a self‐registered questionnaire, it was found that the most problematic aspects for SMEs are ‘organisation’ and ‘evaluation’ . This means the main weaknesses of SMEs related to marketing management lie in the area of planning and implementation as well as control and evaluation of their marketing activities.…”
Section: Improved Marketing and Supply Chain Organisation Methods Formentioning
confidence: 99%
“…Through the use of a self-registered questionnaire, 11 it was found that the most problematic aspects for SMEs are 'organisation' and 'evaluation'. 12 This means the main weaknesses of SMEs related to marketing management lie in the area of planning and implementation as well as control and evaluation of their marketing activities. SMEs appear to analyse the situation of the market, to set a strategy, but they are not able to organise well their resources in order to obtain profits, they do not plan in advance, and just react when there is an effective need.…”
Section: Evaluation Of Marketing Management Capabilities Of Traditionmentioning
confidence: 99%
“…Namely, it has been assumed that, as a result of globalization of food systems, consumers have diverged from the origin and wider contextperspective. However, apart from some notable exceptions (Gellynck & Ku¨hne, 2008;Gellynck & Molna´r, 2009;Gellynck, Molna´r, & Aramyan, 2008;Raynaud, Sauvee, & Valceschini, 2005), TFPs were not extensively analyzed from the chain perspective, and to our knowledge, a dual-consumer versus chain-perspective has never been reported in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%